Reshaping management education for a globalized world - Ossai, Anthony Great; Asabor, Mary Bivweire; Oduma, Justice O.; Oseji, Michael N. (Frontiers in Education, 2025)
The rapid pace of globalization has transformed the operational dynamics of organizations, necessitating a paradigm shift in management education to prepare future leaders for increasingly complex and interconnected business environments. This study critically examines the current state of management education and proposes a comprehensive framework for its transformation in alignment with global standards and expectations. The descriptive survey method was used in the study. The study population included all academic and non-academic staff members at Delta State’s five public universities- Delta State University Abraka, Southern Delta University Ozoro, Dennis Osadebe University Asaba, Federal University of Petroleum Warri, and University of Delta Agbor. The research was descriptive survey method. The Stratified random sampling method was employed to choose 120 non-academic and 160 academic employees. The study was guided by three hypotheses and three research questions. The study used a questionnaire to gather its data. Expert verification resulted in a reliability index of 0.85. The SPSS T-test was used to test the hypotheses at the 0.05 level of significance, while the mean and standard deviation were utilized to address the research questions. Drawing on both empirical and theoretical literature, the paper identifies core challenges including technological disruptions, cultural heterogeneity, curriculum irrelevance, and the widening gap between academic training and industry demands. Also, the study identified the best practices in management education as global competencies and cultural intelligence (CQ), experimental learning and global immersion programs, among others. The paper concludes by offering policy recommendations for academic leaders, curriculum developers, and education policymakers aimed at repositioning management education as a transformative tool for sustainable global development and organizational excellence.